Oryza sativa L. (Rice) in the Ancient Earthen Plasters of Painted Fragments from Bezeklik, China. (4th July 2019) - Dighe, Bhushan; Singh, M. R.; Mani, B. R.; Sahay, Binoy
ABSTRACT: This research reports for the first time the inclusion of Oryza sativa straw, root, and husk as a vegetal additive in the fifth century CE decorative mud plaster of the Buddhist cave of Bezeklik. The investigation is based on the morphological, anatomical, and silica bodies study of the vegetal additives accomplished through a light microscope, stereomicroscope, Fourier-transform infrared spectrophotometer, and scanning electron microscope from the isolated fragments of the painted plaster, transported to India in the nineteenth century and presently housed in National Museum, New Delhi. Studies indicate that loamy sand soil sourced locally for the earthen plaster was mixed with paddy straw in the proportion of 25–30% by volume for cohesion and strength. The excess of sand and absence of clay-size particles in plaster is, however, causing disaggregation of the grains due to lack of cohesion. As locally available materials are preferably used for any plaster works, this study also raises the question – was ancient Bezeklik, now a desert of Northwest China, once a rice-growing area in addition to the crops of Triticum aestivum (wheat), Setaria italica (Foxtail millet), and Hordeum vulgare (barley) reported by many researchers, based on hypothetical environment recreation. This study will help prepare a compatible plaster for the restoration of fragile-painted plaster fragments.